Influence of calcium chloride addition on the properties of emulsions formed with milk protein products : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology - Ye, Aiqian (Massey University, 1999)
The objective of this study was to investigate the effects of added CaCl2 on (i) the adsorption behaviour of caseinate and whey protein concentrate (WPC) at the oil-water interfaces and (ii) the stability of emulsions formed with caseinate or WPC. The relationship between aggregation state of protein, due to Ca2+ binding, and emulsifying properties is discussed. The effects of addition of NaCl to the emulsions containing various concentrations of CaCl2 were also explored. Protein solutions and 30% soya oil, at pH 7.0, were mixed and homogenized at 207/34 bar and 55°C to form emulsions. CaCl2 was added to protein solutions prior to emulsion formation or to the emulsions after they were made. The average particle size (d 32 or d43 ), the surface protein concentration, the composition of protein adsorbed layer at the interface and the creaming stability of emulsions were determined. The microstructure of emulsions was observed using the confocal laser microscopy. The droplet sizes of emulsions made with sodium caseinate or WPC were similar and were independent of the protein concentration at concentration above 0.5%. The surface protein concentration of emulsions made with sodium caseinate, WPC or calcium caseinate generally increased with increase in the protein concentration, although the trends were different. The emulsions made with calcium caseinate had higher (d32 and surface protein concentration than that of sodium caseinate or WPC. In emulsions made with sodium caseinate at low protein concentrations, the adsorption of β-casein occurred in preference to αs -casein, whereas αs- (αs1- + αs2 -)casein was found to adsorb in preference to β-casein at high protein concentrations. In calcium caseinate emulsions, the αs -casein was adsorbed in preference to β-casein at all concentrations. In emulsions made with WPC, β-lactoglobulin adsorbed slightly in preference to α-lactalbumin. In emulsions made with mixtures of sodium caseinate and WPC (1:1), the adsorption of whey proteins occurred in preference to caseins at low concentrations (< 3%), whereas caseins were adsorbed in preference to whey protein at high concentrations. In emulsions made with calcium caseinate or WPC, the creaming stability of emulsions followed mainly the changes in particle size of emulsions. However, the creaming stability of emulsions made with sodium caseinate decreased markedly as the caseinate concentrations were increased above 2.0%. This was attributed to depletion flocculation occurring in these emulsions. Whey proteins did not retard this instability, due to depletion flocculation, in emulsions made with mixtures of caseinate and WPC When CaCl2 was added prior to or after emulsion formation, the (d43 and surface protein concentration increased with increasing CaCl2 concentration in emulsions made with 0.5 and 3.0% sodium caseinate. The adsorption of αs -casein increased with increase in the concentration of CaCl2 , with a corresponding decrease in the adsorption of β-casein. The creaming stability of emulsions made with 0.5% caseinate decreased with increasing CaCl2 concentration. However, the creaming stability increased with CaCl2 concentration in 3.0% caseinate emulsion. The destabilising effects of CaCl2 in emulsions made with sodium caseinate were reduced by the addition of 200 mM NaCl. Addition of CaCl2 to protein solutions prior to emulsion formation increased the d43 and surface protein concentration in emulsions made with 0.5 or 3.0% WPC. In this case, the adsorption of β-lactoglobulin occurred slightly in preference to α-lactalbumin. The creaming stability of emulsions decreased with increase in the concentration of CaCl2 . The addition of CaCl2 to emulsions after emulsion formation also resulted in increases in and surface protein concentration of emulsions made with 0.5% WPC and formation of gel-like network structure at high CaCl2 concentrations. However, the stability of emulsion made with 3.0% WPC was not affected by the addition of CaCl2 . Different aggregation mechanisms are involved depending upon whether Ca2+ is added to protein solution before emulsification or to the emulsion after its formation. Addition of Ca2+ to protein solution may lead to decrease in emulsifying capacity and subsequently result in protein bridging flocculation between emulsion droplets. Ca2+ bridging flocculation between emulsion droplets may be formed in emulsions that have Ca2+ added. The change in aggregation state of caseinate due to Ca2+ binding could retard the instability of emulsion due to depletion flocculation. The protein unfolding at the surface of emulsions made with low whey protein concentrations may promote the protein-Ca-protein bridges forming between protein-coated emulsion droplets, consequently forming gel-like network structure in emulsions.
Keywords: Emulsions; Calcium chloride; Milk proteins; Food